Conformational Behavior of CH 3 OC(O)SX (X = CN and SCN) Pseudohalide Congeners. A Combined Experimental and Theoretical Study - Torrico Vallejos, Sonia (2010)
Methyl 4-chloro-5-phenyl-1,3-oxazole-2-carboxylate (MCPOC) has been synthesized and isolated in cryogenic matrices (argon and xenon). FTIR spectroscopy studies on the matrix isolated compound, supported by DFT(B3LYP)/ 6-311++G(d,p) calculations, allow for the identification of two low-energy conformers (I and II) of the molecule, which differ from each other in the orientation of the ester group relative to the oxazole ring. In both these conformers, the ester moiety is in the s-cis configuration (OdCsOsCH3 dihedral: 0°). Conformer II is ca. 3.0 kJ mol-1 higher in energy than form I in the gas phase. Two additional higher energy conformers, III and IV, with relative energies of ca. 30 and 45 kJ mol-1, respectively, were predicted to exist by the calculations, corresponding to structures where the ester group is in an approximately s-trans arrangement. Annealing of the compound isolated in xenon at 60 K led to aggregation and simultaneous reduction of the population of I compared to that of the more polar conformer II. These results suggest the inversion of the order of stability of the two conformers in that matrix, eventually accompanied by a higher trend of conformer I to aggregate. Full assignment of the observed infrared bands to the two experimentally accessible conformers was carried out for the matrix isolated monomeric species. In addition, the infrared spectra of the neat compound in the low-temperature (10 K) amorphous and crystalline phases, as well as the infrared and Raman spectra of the crystal at room temperature were also obtained and assigned.